2019
DOI: 10.1038/s41598-019-41642-y
|View full text |Cite|
|
Sign up to set email alerts
|

All semiconductor enhanced high-harmonic generation from a single nanostructured cone

Abstract: The enhancement and control of non-linear phenomena at a nanometer scale has a wide range of applications in science and in industry. Among these phenomena, high-harmonic generation in solids is a recent focus of research to realize next generation petahertz optoelectronic devices or compact all solid state EUV sources. Here, we report on the realization of the first nanoscale high harmonic source. The strong field regime is reached by confining the electric field from a few nanojoules femtosecond laser in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 39 publications
3
26
0
2
Order By: Relevance
“…It was demonstrated that both the confinement of electron motion and the inhomogeneous character of laser electric field play an important role in the HHG process and lead to a significant increase of the harmonic cutoff. Field enhancement of plasmon nanoparticles deposited on substrate leads to enhanced second and third harmonics generation, as well as higher-order harmonics, which was reported in several works [31][32][33][34][35][36][37][38].…”
Section: Comparison Of Harmonic Emission From Different Plasmas Contasupporting
confidence: 53%
“…It was demonstrated that both the confinement of electron motion and the inhomogeneous character of laser electric field play an important role in the HHG process and lead to a significant increase of the harmonic cutoff. Field enhancement of plasmon nanoparticles deposited on substrate leads to enhanced second and third harmonics generation, as well as higher-order harmonics, which was reported in several works [31][32][33][34][35][36][37][38].…”
Section: Comparison Of Harmonic Emission From Different Plasmas Contasupporting
confidence: 53%
“…Furthermore, as a result of the strong electric field, coherent electron and hole dynamics are driven, which lead to intra- and interband high harmonic generation (HHG) via nonlinear intraband currents and polarization fields upon electron-hole recombination, respectively [ 9 ]. After the first experimental demonstration of HHG from ultrashort, mid-IR laser pulses in ZnO [ 10 ], the dependence of HHG on the ZnO lattice symmetry [ 11 , 12 ] and HHG from tailored ZnO nanostructures [ 13 , 14 , 15 , 16 ] have been investigated. Furthermore, HHG in ZnO was used to determine the carrier envelope phase (CEP) of few cycle mid-IR laser pulses [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This characterization method simplifies drastically the experimental setup compared to interferometry, given that the source has sufficient peak power to drive high harmonic generation from solids. Note that there has been recent progresses for driving HHG from solids with high repetition rate IR laser systems delivering ∼10 nanojoules pulses through the enhancement of the process with nanostructures [46]. Combined with our approach, this could be useful to characterize the CEP fluctuations of high repetition rate mid-IR laser sources.…”
Section: Introductionmentioning
confidence: 91%